Ultrasound screening for abdominal aortic aneurysms: A feasibility study in selected male population attending the outpatient clinics of the Regional Hospital of Lugano, Switzerland (Swiss Medical Weekly, 2017)
QUESTION UNDER STUDY This pilot study aimed to assess the feasibility, acceptance and costs of an ultrasound scan screening programme for abdominal aortic aneurysms (AAA) in the elderly male population resident in Canton Ticino, Switzerland. METHODS The target population were male patients aged 65–80 years who attended the outpatient clinics of the Lugano Regional Hospital in 2013. The patients showing interest were contacted by phone to verify their eligibility and fix the appointment for the ultrasound scan of the abdominal aorta. Patients with recent examinations suitable for AAA detection were excluded. Aneurysm was defined as an abdominal aorta with sagittal and/or axial diameter ≥30 mm. Patients’ characteristics and study results were presented as descriptive statistics. The chi-squared test was used to compare categorical variables with p